CALAMOS Closed-End Funds (CHI, CHY, CSQ, CGO) Announce Monthly Dividends (PR Newswire, 2006)
The Funds have level rate distribution policies paying monthly distributions at the stated rates. Distributions paid may include net investment income, net realized short-term capital gains and, if necessary, return of capital. In addition, distributions may include net realized long- term capital gains as permitted by the Investment Company Act of 1940. There is no guarantee that the Funds will realize capital gains in any given year. Distributions are subject to re-characterization for tax purposes after the end of the fiscal year. All shareholders with taxable accounts will receive written notification regarding the components and tax treatment for distributions via Form 1099-DIV. Distributions from the Funds are generally subject to Federal income taxes. For purposes of maintaining the level rate distribution policy, the Funds may realize short-term capital gains on securities that, if sold at a later date, would have resulted in long-term capital gains. Maintenance of a level rate distribution policy may increase transaction and tax costs associated with the Funds.